Pregled brušenja z velikimi hitrostmi in učinkovitih abrazivnih orodij - Krajnik, Peter (Strojniški vestnik, 2004)
This paper reviews the modern aspects of grinding with regards to enhanced productivity and manufacturing quality demands. The basic mechanism of grinding and the applications for the state-of-the-art technology of high-speed grinding (HSG) with high-performance grinding wheels are presented.In addition to the improvements in the technology associated with HSG, the grinding machine-tool, the coolant system and the process monitoring also need to adapt to high-speed machining. In addition, the ground-surface integrity and the economic efficiency of HSG are also briefly discussed.
Keywords: brušenje zelo hitro; abrazivi; integriteta površin; brušenje; brusi